GROWTH RESPONSE AND YIELD OF KAILAN (Brassica Oleraceae) AGAINST ORGANIC LIQUID EXCELLENT PLANT HORMONE (HANTU) AND UREA FERTILIZER APPLICATION - Muhammad Khaidir Rambe; Syafrizal Hasibuan; Lokot Ridwan Batubara (Bernas : Jurnal Penelitian Pertanian, 2018)
This research was arranged based on Factorial Randomized Design (RAK) with two treatmentfactors and three replications, the first factor was the application of liquid liquid organic fertilizer (H) consisting of 4 levels ie H0 (0 ml /l water/plot), H1 (1, 0 ml/ l water/plot), H2 (2.0 ml/ l water/plot), H3 (3.0 ml/ l water / plot) and second fator is Urea fertilizer consisting of 3 levels ie U0 (Control), U1 (14.4 g / plot) and U2 (28.8 g/plot). The result of research that the treatment of liquid organic fertilizer of plant hormone has a significant effect on the growth and production of mustard kailan plant. The best treatment was obtained at treatment (H3) resulting in plant height 37,90 cm, number of leaves 13,55 pieces, production per plant 169,00 g and production per plot 3.06 kg. Treatment The treatment of urea fertilizer affects the growth and production of mustard kailan plants. The best treatment was obtained at concentration 3 ml / l water (H3) yield 37,90 cm height, leaf amount 12,12 strands, production per plant 159,26 g and production per plot 2,77 kg. The interaction of organic fertilizer of liquid hormone of superior plant and urea fertilizer showed no significant effect on the growth and production of mustard crop kailan.